Topographic changes as predictor for determining anterior corneal curvature stabilization point subsequent to pterygium excision using controlled partial avulsion fibrin glue technique - Hilmi, Mohd Radzi; Maruziki, Nur Nabilah; Mohd Kamal, Khairidzan; Che Azemin, Mohd Zulfaezal; Norazmar, Nur Ain; Nasir, Mardhiah Syazwani; Musa, Nur Hidayah (International Islamic University Malaysia (IIUM), 2019)
Introduction: This paper aimed to determine the corneal stabilization point using corneal topographic approach subsequent to pterygium excision using controlled partial avulsion fibrin glue technique. Methods: Ninety-three eyes of 93 patients who had undergone primary pterygium excision surgery were retrospectively reviewed. Topographic changes, based on changes in Simulated-K (SimK), were determined by having four (4) follow-up sessions (at 1st, 3rd, 6th, and 12th month post-surgical. The parameter studied was the degree of astigmatism measured with Zeiss ATLAS 995 corneal topographer. Three measurements were taken and only the measurement with the best image quality was accepted. These measurements were conducted by a single operator and performed by the same operator for each follow-up visit. All participants then underwent pterygium excision performed by a consultant ophthalmologist (KMK). RM-ANOVA and Bonferroni post-hoc analysis were employed to evaluate the difference between sessions with SimK. Results: Topographic changes revealed corneal stabilization point at 3rd month post-operatively. Significance improvements for corneal astigmatism was noted for the 1st and the 3rd months (both P< 0.001), followed by insignificant changes towards the remaining 6th and 12th months visits (both P> 0.05). Conclusions: Anterior corneal curvature stabilization point is obtained at 3rd months of post-surgical procedure.Thus we suggest other refractive procedures are safe to be performed after the 3rd month of pterygium excision.